Gen Alpha Engagement Model: The Role of Influencer Skill, Authenticity, and Interactivity with Relatability as a Mediating Mechanism - Dwi Erlin Effendi; Mohamad Rifqy Roosdhani; Ali Ali (Journal of Accounting, Management, and Economics Research (JAMER), 2026)
The rise of short-form video social media has strengthened the role of influencers in shaping audience engagement, particularly among Generation Alpha, a digitally native generation accustomed to real-time communication and personalized digital experiences. This study examines the influence of influencer skill, authenticity, and interactivity on customer engagement, with relatability as a mediating variable. Using a quantitative survey approach, data were collected from Generation Alpha users who actively consume influencer content on short-video platforms. Responses were measured using a five-point Likert scale and analyzed through Structural Equation Modeling (SEM). The findings show that influencer skill, authenticity, and interactivity do not significantly affect customer engagement directly. However, all three variables positively and significantly influence relatability. Relatability also has a strong positive effect on customer engagement and fully mediates the relationship between influencer characteristics and engagement. These results suggest that Generation Alpha engagement is driven less by influencers’ technical or functional attributes and more by psychological closeness and relational connection. This study contributes to influencer marketing literature by emphasizing relatability as a key mechanism in building meaningful audience engagement among younger digital consumers, while highlighting the importance of emotionally resonant communication in contemporary social media marketing contexts for future strategic applications and research.